2014
DOI: 10.1371/journal.pone.0094272
|View full text |Cite
|
Sign up to set email alerts
|

EIAV-Based Retinal Gene Therapy in the shaker1 Mouse Model for Usher Syndrome Type 1B: Development of UshStat

Abstract: Usher syndrome type 1B is a combined deaf-blindness condition caused by mutations in the MYO7A gene. Loss of functional myosin VIIa in the retinal pigment epithelia (RPE) and/or photoreceptors leads to blindness. We evaluated the impact of subretinally delivered UshStat, a recombinant EIAV-based lentiviral vector expressing human MYO7A, on photoreceptor function in the shaker1 mouse model for Usher type 1B that lacks a functional Myo7A gene. Subretinal injections of EIAV-CMV-GFP, EIAV-RK-GFP (photoreceptor spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 39 publications
1
80
0
Order By: Relevance
“…The results of the first phase 3 human gene therapy randomized clinical trial, voretigene neparvovec for the treatment of LCA2, has been recently published (56). Furthermore, more than 10 clinical trials for retinal degeneration have either been completed or initiated (57)(58)(59)(60)(61)(62)(63). A multitude of additional candidates for gene therapy with already established animal models exist and RPGRIP1 is one such example (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the first phase 3 human gene therapy randomized clinical trial, voretigene neparvovec for the treatment of LCA2, has been recently published (56). Furthermore, more than 10 clinical trials for retinal degeneration have either been completed or initiated (57)(58)(59)(60)(61)(62)(63). A multitude of additional candidates for gene therapy with already established animal models exist and RPGRIP1 is one such example (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Although this response is promising as read-out for MYO7A function in photoreceptors, it should be noted that, unlike the above mutant phenotypes, it has only been observed in one allele of shaker1 mice, . The specific mutation underlying this allele, and the effect that the mutation has on protein structure and levels are not known, except that mutant MYO7A protein is detectable (Zallocchi et al 2014). The same investigators have identified an increased susceptibility to light-induced photoreceptor degeneration in Myo7a sh1-11J mice (Peng et al 2011), which is the converse finding to that mentioned above for the null shaker1 allele, Myo7a sh1-4626SB (Lopes et al 2011).…”
mentioning
confidence: 82%
“…Toxicity and biodistribution were assessed in a 3-month study of the SAR421869 construct following a single subretinal injection in rhesus macaques (Macaca mulatta) (Zallocchi et al 2014) prior to entering into clinical trials. The ongoing phase I/II trials (NCT01505062, NCT02065011) are evaluating the safety of this integrating lentiviral vector.…”
Section: Myo7a Gene Therapymentioning
confidence: 99%